1997
DOI: 10.1023/a:1005740823703
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The gene encoding green fluorescent protein (GFP) from Aequorea victoria was resynthesized to adapt its codon usage for expression in plants by increasing the frequency of codons with a C or a G in the third position from 32 to 60%. The strategy for constructing the synthetic gfp gene was based on the overlap extension PCR method using 12 long oligonucleotides as the starting material and as primers. The new gene contains 101 silent nucleotide changes compared to its wild-type counterpart used in this study. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Since all cp genomes have high AT content, AT biased mutational pressure is believed to be the factor responsible for codon usage bias. Previous studies demonstrated that there existed a significant relationship between codon usage bias and gene expression level [57], [58], which suggested stronger natural selection constraints on highly expressed genes to optimize translation efficiency using major codons [59]. Information about the rare and preferred codons can be effectively used for enhancing gene expression by optimizing synonymous codons, which may provide us a further understanding of synthesis and metabolism of secondary metabolites in D. stramonium .…”
Section: Discussionmentioning
confidence: 99%
“…Since all cp genomes have high AT content, AT biased mutational pressure is believed to be the factor responsible for codon usage bias. Previous studies demonstrated that there existed a significant relationship between codon usage bias and gene expression level [57], [58], which suggested stronger natural selection constraints on highly expressed genes to optimize translation efficiency using major codons [59]. Information about the rare and preferred codons can be effectively used for enhancing gene expression by optimizing synonymous codons, which may provide us a further understanding of synthesis and metabolism of secondary metabolites in D. stramonium .…”
Section: Discussionmentioning
confidence: 99%
“…[45,46]) and may also be associated with the codon bias of chloroplast protein-coding genes and hence the regulation of gene expression (e.g. [45,46]).…”
Section: Resultsmentioning
confidence: 99%
“…[45,46]) and may also be associated with the codon bias of chloroplast protein-coding genes and hence the regulation of gene expression (e.g. [45,46]). AT-rich regions in the Wollemia chloroplast genome include intergenic (67.88%), protein-coding (62.41%) and intronic (62.39%) regions, while rRNAs (45.75%) and tRNAs (46.47%) have a much lower AT content.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Liu et al (113) demonstrated the induction of apoptosis (programmed cell death) by three mutant GFPs in four mammalian cell lines. GFP toxicity has also been noted in plants (100,108), particularly A. thaliana (107), although Niwa and co-workers (79) have since demonstrated nontoxic high-level expression of a synthetic, codon-optimized GFP in Arabidopsis.…”
Section: Codon Optimization and The Use Of More Active Promotersmentioning
confidence: 99%